Catalytic Hydrothermal Liquefaction of Mango Waste over Template-Synthesized NiFe₂O₄/Biochar Catalyst - Abdul-Hameed Bukhari Auwal; Atuman Samaila Joel; Yusuf Olabode Raji; Abubakar Muhammad Hammari (Darul Yasin Al Sys, 2026)
Hydrothermal liquefaction (HTL) offers a promising pathway for converting wet organic waste into liquid fuels; however, the high oxygen content of bio-crude derived from fruit waste remains a major limitation. This study aims to valorize mango fruit waste (MFW) into upgraded bio-crude oil through catalytic HTL using a template-synthesized activated biochar-supported NiFe₂O₄ bimetallic catalyst. The feedstock and catalyst were characterized using proximate and ultimate analyses, Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), scanning electron microscopy (SEM), X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET) surface area analysis, and gas chromatography–mass spectrometry (GC–MS). Mango fruit waste showed favorable hydrothermal conversion characteristics, including high volatile matter content, a carbon content of 48.07 wt%, and a higher heating value (HHV) of 14.32 MJ kg⁻¹. The incorporation of the NiFe₂O₄-activated biochar catalyst substantially improved bio-crude quality compared with non-catalytic HTL, increasing the carbon content to 63.53 wt% and the HHV to 16.66 MJ kg⁻¹. GC–MS analysis revealed a marked compositional shift toward aromatic hydrocarbons, phenolic compounds, and nitrogen-containing heterocycles, indicating enhanced deoxygenation, hydrogen transfer, and aromatization reactions promoted by the bimetallic catalyst. The study concludes that template-engineered biochar-supported NiFe₂O₄ catalysts are effective for upgrading oxygen-rich intermediates during fruit waste HTL. These findings contribute to sustainable waste valorization and biofuel production by demonstrating the potential of mango fruit waste as a viable feedstock for producing improved bio-crude oil.